The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/s21248334
|View full text |Cite
|
Sign up to set email alerts
|

Discussion and Analysis of Dumbbell Defect-Ground-Structure (DB-DGS) Resonators for Sensing Applications from a Circuit Theory Perspective

Abstract: Microstrip transmission lines loaded with dumbbell defect-ground-structure (DB-DGS) resonators transversally oriented have been exhaustively used in microwave circuits and sensors. Typically, these structures have been modelled by means of a parallel LC resonant tank series connected to the host line. However, the inductance and capacitance of such model do not have a physical meaning, since this model is inferred by transformation of a more realistic model, where the DB-DGS resonator, described by means of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It can be shown that the equivalent circuit model of the structure when the symmetry plane of the DGS is orthogonal to the loaded microstrip line is identical to the circuit model of a CSRR-loaded TL shown in Fig. 1 d 18 . Therefore, it would be instructive to extract the parameters of the equivalent circuit model of the sensor based on the dumbbell-shape DGS and compare it with those of the sensor based on a single-ring CSRR.…”
Section: Crack Detection Using Defected Ground Structuresmentioning
confidence: 95%
See 1 more Smart Citation
“…It can be shown that the equivalent circuit model of the structure when the symmetry plane of the DGS is orthogonal to the loaded microstrip line is identical to the circuit model of a CSRR-loaded TL shown in Fig. 1 d 18 . Therefore, it would be instructive to extract the parameters of the equivalent circuit model of the sensor based on the dumbbell-shape DGS and compare it with those of the sensor based on a single-ring CSRR.…”
Section: Crack Detection Using Defected Ground Structuresmentioning
confidence: 95%
“…Among various methods of microwave sensing, sensing based on microwave resonators is perhaps the most widely used method that benefits from high sensitivity, relatively simple application, and scalability to other frequencies in the electromagnetic spectrum. In this method, usually, variations of the resonance frequency of a microwave resonator due to changes in the variable to be sensed are considered as the output variable of the sensor 13 – 18 . For applications that require very high sensitivity, high-quality factor resonators such as waveguide cavities are best suited 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Designing a filter with the perspective of an LC-equivalent circuit is one of the most representative methods [10][11][12]. Simplified equivalent circuits for the DS-DG structure and the GCS resonator are shown in Figure 2 [13,14]. The DS-DG structure can be represented by a parallel LC-resonator series connected on the line, and the GCS resonator can be expressed via a series LC-resonator shunt connected from the line.…”
Section: Configuration Of a Ds-dg Cmr Filtermentioning
confidence: 99%
“…A way to improve this filter is to add a defective ground structure (DGS) and quarter wavelength stubs. The DGS is an etched-out pattern defect created on the ground plane of a printed microstrip board, which can help expand the filter's bandwidth, improve the stripline filter's parameters and compact the circuit size [7]. The quarter wavelength stubs can be made for a notch filter [8] which can attenuate specific frequencies and form the lowpass filtering response, improving the filter's performance in the out-band frequency band.…”
Section: Data Comparison and Analyze The Problemmentioning
confidence: 99%